An Innovative Approach to Teaching the System of Linear Equations Module - Aziza Turapova (Journal of Higher Education and Academic Advancement, 2024)
In solving the system of linear equations, it is important to improve the ability of students to think quickly, to facilitate the process of deep logical thinking, and to guide them through the algorithm of the problem.